2008
DOI: 10.1038/nature07488
|View full text |Cite
|
Sign up to set email alerts
|

HITS-CLIP yields genome-wide insights into brain alternative RNA processing

Abstract: SummaryProtein-RNA interactions play critical roles in all aspects of gene expression. Here we develop a genome-wide means of mapping protein-RNA binding sites in vivo, by high throughput sequencing of RNA isolated by crosslinking immunoprecipitation (HITS-CLIP). HITS-CLIP analysis of the neuron-specific splicing factor Nova2 revealed extremely reproducible RNA binding maps in multiple mouse brains. These maps provide genome-wide in vivo biochemical footprints confirming the previous prediction that the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

46
1,246
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,233 publications
(1,322 citation statements)
references
References 50 publications
46
1,246
3
2
Order By: Relevance
“…Nucleotide bases absorb UV light at this wavelength, generating free radicals that react with amino acids at very short range, forming covalent bonds. After immunoprecipitation, RNAs bound to the targeted RBP can be identified by next-generation sequencing (crosslinking, immunoprecipitation and sequencing, CLIP-seq) (Licatalosi et al 2008;Milek et al 2012). In a complementary fashion, the repertoire of proteins that bind to polyadenylated RNAs in living cells can be determined by RNA interactome capture (Baltz et al 2012;Castello et al 2012Castello et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotide bases absorb UV light at this wavelength, generating free radicals that react with amino acids at very short range, forming covalent bonds. After immunoprecipitation, RNAs bound to the targeted RBP can be identified by next-generation sequencing (crosslinking, immunoprecipitation and sequencing, CLIP-seq) (Licatalosi et al 2008;Milek et al 2012). In a complementary fashion, the repertoire of proteins that bind to polyadenylated RNAs in living cells can be determined by RNA interactome capture (Baltz et al 2012;Castello et al 2012Castello et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Their study demonstrated that the position of Nova binding determines the outcome of alternative splicing. Interestingly, many Nova-2 binding sites are localized to 3′ untranslated regions (3′ UTRs), suggesting that Nova regulates alternative polyadenylation in the brain [43]. Finally, they combined CLIP, exon-junction splicing microarrays, HITS-CLIP, and more sophisticated bioinformatics identified a set of 700 Nova-dependent alternatively spliced exons and a smaller number of alternative 3′ UTRs in the mouse brain [44].…”
Section: The Nova Familymentioning
confidence: 99%
“…Finally, they combined CLIP, exon-junction splicing microarrays, HITS-CLIP, and more sophisticated bioinformatics identified a set of 700 Nova-dependent alternatively spliced exons and a smaller number of alternative 3′ UTRs in the mouse brain [44]. The identification of these Nova target genes predicts a role of Nova in synaptic function, especially in mediating inhibitory responses and suggests potential association of Nova with other neurological diseases [43,44].…”
Section: The Nova Familymentioning
confidence: 99%
“…Deciphering this code requires the comprehensive identification of RBP binding sites. Since a RBP can have thousands of functional target sites (Licatalosi et al, 2008;Hafner et al, 2010), experiments need to reliably detect RBP-mRNA interactions on a transcriptome wide scale and resolve sites at nucleotide resolution. Previously, RIP-chip (RBP ImmunoPrecipitation and microarray analysis) (Keene et al, 2006) has identified numerous functional mRNA targets of RBPs, including HuR de Silanes et al, 2004;Mukherjee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%